Calcium Sensing Receptor-Related Pathway Contributes to Cardiac Injury and the Mechanism of Astragaloside IV on Cardioprotection - Lu, Meili; Leng, Bin; He, Xin; Zhang, Zhen; Wang, Hongxin; Tang, Futian (Frontiers in Pharmacology, 2018)
Activation of calcium sensing receptor (CaSR) contributes to cardiac injury, but the underlying mechanism has not yet been examined. Astragaloside IV (AsIV) was previously reported to exhibit protective effects against various myocardial injuries. The aim of the present study was to investigate the underlying mechanism of CaSR in cardiac hypertrophy and apoptosis and to evaluate whether the protective effect of AsIV against myocardial injury is associated with CaSR and its related signaling pathway. In vivo and in vitro myocardial injury was induced by isoproterenol (Iso) or GdCl3 (a CaSR agonist) in rats and heart H9C2 cells. Cardiac cell hypertrophy, apoptosis, function, mitochondrial membrane potential (MMP), mitochondrial ultrastructure, and [Ca2+]i, as well as the protein expression of CaSR, calcium/calmodulin-dependent protein kinase II (CaMKII), calcineurin (CaN), sarcoplasmic reticulum Ca2+-ATPase2a (SERCA2a) and the inositol 1,4,5-trisphosphate receptor (IP3R), were measured in vivo and/or in vitro. The results showed that AsIV attenuated cardiac hypertrophy and apoptosis and attenuated impairments in cardiac function, mitochondrial structure and MMP induced by Iso or GdCl3 in rat myocardial tissue and H9C2 cells. Importantly, AsIV treatment inhibited the enhancement of [Ca2+]i and CaSR expression induced by Iso or GdCl3, an effect similar to that of the CaSR antagonist NPS2143. In addition, AsIV treatment repressed CaSR, CaMKII and CaN activation and inhibited NFAT-3 nuclear translocation. Mechanistic analysis using lentiviral infection showed that CaSR overexpression activated the CaMKII and CaN signaling pathways and that this response was enhanced by Iso. The results suggested that CaSR-mediated changes in [Ca2+]i and CaMKII and CaN signaling pathways contribute to cardiac hypertrophy and apoptosis and are involved in the protective effect of astragaloside IV against cardiac injury